Science seminar: Mitigation potentials in the livestock sector - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
On November 13, 2012, Mario Herrero, based with International Livestock Research Institute (ILRI) gave a live-streamed science seminar entitled: "Mitigation potentials in the livestock sector". Organised by ILRI and the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS), Herrero gave an up-to-date overview of ways the livestock sector in developing countries can help mitigate greenhouse gas emissions. Read more on CCAFS blog: http://ow.ly/rhU4O